A Temperature-Precipitation Based Leafing Model and Its Application in Northeast China - Li, Rong-Ping; Zhou, Guang-Sheng (PLOS ONE, 2012)
Plant phenology models, especially leafing models, play critical roles in evaluating the impact of climate change on the primary production of temperate plants. Existing models based on temperature alone could not accurately simulate plant leafing in arid and semi-arid regions. The objective of the present study was to test the suitability of the existing temperature-based leafing models in arid and semi-arid regions, and to develop a temperature-precipitation based leafing model (TP), based on the long-term (i.e., 12–27 years) ground leafing observation data and meteorological data in Northeast China. The better simulation of leafing for all the plant species in Northeast China was given by TP with the fixed starting date (TPn) than with the parameterized starting date (TPm), which gave the smallest average root mean square error (RMSE) of 4.21 days. Tree leafing models were validated with independent data, and the coefficient of determination (R2) was greater than 0.60 in 75% of the estimates by TP and the spring warming model (SW) with the fixed starting date. The average RMSE of herb leafing simulated by TPn was 5.03 days, much lower than other models (>9.51 days), while the average R2 of TPn and TPm were 0.68 and 0.57, respectively, much higher than the other models (<0.22). It indicates that TPn is a universal model and more suitable for simulating leafing of trees and herbs than the prior models. Furthermore, water is an important factor determining herb leafing in arid and semi-arid temperate regions.